2015
DOI: 10.13065/jksdh.2015.15.06.973
|View full text |Cite
|
Sign up to set email alerts
|

Correlation with subjective oral health status and food preference in elderly people

Abstract: Objectives:The purpose of the study is to investigate the correlation with subjective oral health status and food preference in elderly people. Methods: Data were extracted from the fifth Korea National Health and Nutrition Survey 2010-2012. The survey data included general characteristics of the subjects, food preference, and subjective oral health status. Food preference was analyzed by assigning score to 63 food categories. The subjective oral health status consisted of toothache within a month, self-percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The elderly with mastication difficulties preferred soft food, prioritizing food that would be easier to masticate over those with good nutritional value [ 32 ]. Those who perceived their oral health as poor had a low preference for all foods except grains, oils, and sugars; those with chewing and chewing problems had a low preference for all foods; and those with speech discomfort had a low preference for all foods except oils and sugars [ 33 ]. The elderly with good oral health preferred vegetables and fruits [ 34 ], and it has been reported that the higher the number of existing natural teeth, the higher the intake of iron, potassium, thiamine, riboflavin, niacin, vitamin C, and protein [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elderly with mastication difficulties preferred soft food, prioritizing food that would be easier to masticate over those with good nutritional value [ 32 ]. Those who perceived their oral health as poor had a low preference for all foods except grains, oils, and sugars; those with chewing and chewing problems had a low preference for all foods; and those with speech discomfort had a low preference for all foods except oils and sugars [ 33 ]. The elderly with good oral health preferred vegetables and fruits [ 34 ], and it has been reported that the higher the number of existing natural teeth, the higher the intake of iron, potassium, thiamine, riboflavin, niacin, vitamin C, and protein [ 35 ].…”
Section: Discussionmentioning
confidence: 99%